Erzählen als multimodale Aktivität – zur Einführung in das Themenheft - Zima, Elisabeth; Weiß, Clarissa (Linguistik Online, 2020)
This special issue of Linguistik online is dedicated to the study of storytelling in face-to-face interaction. More specifically, the individual contributions to this special issue approach conversational storytelling from a multimodal perspective and provide analyses on the fine-grained coordination of verbal, para-verbal, and nonverbal action in face-to-face storytelling. This introduction first frames the individual contributions by providing an overview of the current topics and open research questions in the developing field of multimodal storytelling research. All individual papers are then briefly summarized and discussed in terms of their commonalities and their contribution to the developing field of multimodally-oriented research on conversational storytelling.